MEDIA â€œAUDIO VISUALâ€ UNTUK PEMBELAJARAN KEMAHIRAN MENULIS (IMLAâ€™) - Munawwaroh, Ela Isnani (Universitas Ahmad Dahlan, 2021)
Abstract: The ability of students in Islamic universities to write Arabic correctly is very important. Therefore, it is very important to have learning related to tahsinul kitabah or improving Arabic writing. The problem that the writer finds in the process of learning tahsinul kitabah is that there are still many students who have very low writing skills in Arabic. This is partly due to the previous educational background. For this reason, a learning innovation is needed that can help students improve their writing skills even for those who do not have an educational background in previous Islamic religious schools. This paper contains a study of several learning media theories which are mixed in a learning media design. The results of this study, the authors produced an audiovisual learning media for imla 'learning, namely silent audio-visual media, in the form of books / sheets and sound (audio).Key Words: Instructional media, audio-visual, imlaâ€™Â Abstrak: Kemampuan mahasiswa di perguruan tinggi Islam dalam menulis tulisan berbahasa Arab sangat penting. Oleh karena itu, sangat diperlukan adanya pembelajaran terkait tahsinul kitabah atau memperbaiki tulisan berbahasa Arab. Permasalahn yang penulis temukan dalam proses pembelajaran tahsinul kitabah adalah masih banyaknya mahasiswa yang memiliki kemampuan menulis tulisan berbahasa Arab sangat rendah. Hal itu di antaranya disebabkan oleh latar belakang pendidikan yang ditempuh sebelumnya. Untuk itu diperlukan adanya suatu inovasi pembelajaran yang bisa membantu mahasiswa meningkatkan kemampuan menulis mereka bahkan bagi mereka yang tidak memiliki latar pendidikan di sekolah agama Islam sebelumnya. Tulisan ini berisi kajian terhadap beberapa teori media pembelajaran yang diramu dalam suatu desain media pembelajaran. Hasil dari kajian tersebut, diperoleh sebuah media pembelajaran audiovisual untuk pembelajaran imlaâ€™, yaitu media audio visual diam, berupa buku/lembaran dan suara (audio).Kata kunci: Media pembelajaran, audio-visual, imlaâ€™